2005
DOI: 10.1158/1078-0432.ccr-04-2244
|View full text |Cite
|
Sign up to set email alerts
|

First Clinical Experience with α-Emitting Radium-223 in the Treatment of Skeletal Metastases

Abstract: Purpose: The main goals were to study the safety and tolerability of the a-emitter radium-223 ( 223 Ra) in breast and prostate cancer patients with skeletal metastases. In addition, pain palliation was evaluated. Experimental Design: Fifteen prostate and 10 breast cancer patients enrolled in a phase I trial received a single i.v. injection of 223 Ra. Five patients were included at each of the dosages: 46, 93, 163, 213, or 250 kBq/kg and followed for 8 weeks. Palliative response was evaluated according to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
280
2
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(300 citation statements)
references
References 35 publications
11
280
2
7
Order By: Relevance
“…The safety of 223 Ra was also demonstrated since grade 3 and 4 myelotoxicity were infrequent (37,38). Nadir of myelotoxicity occurred at 2-4 weeks after treatment and recovery was in 24 weeks (34).…”
Section: % P<0001)mentioning
confidence: 93%
See 1 more Smart Citation
“…The safety of 223 Ra was also demonstrated since grade 3 and 4 myelotoxicity were infrequent (37,38). Nadir of myelotoxicity occurred at 2-4 weeks after treatment and recovery was in 24 weeks (34).…”
Section: % P<0001)mentioning
confidence: 93%
“…However, more common nonhematological toxicities, such as diarrhea, nausea, vomiting and fatigue, were more frequent than with other novel therapies, such as abiraterone and enzalutamide, although easily manageable (33). In Nilsson et al's studies, constipation was reported more frequently than in the placebo-treated group (37,38). Patients pretreated with docetaxel or having a greater extent of osseous disease (>6 metastases) seemed to have a slightly higher risk of myelosuppression.…”
Section: % P<0001)mentioning
confidence: 93%
“…The neutrophils were more frequently affected than the platelets, whereas for β -emitters thrombocytopenia is often the clinically important toxicity. The most common forms of adverse event were transient diarrhea, fatigue, nausea and vomiting (Nilsson et al, 2005a). In clinical studies, 223 RaCl 2 has demonstrated a highly significant improvement on patient overall survival, with mild side effects owing to its localized tissue penetration (2-10 cells).…”
Section: Iiii 223 Ra-chloridementioning
confidence: 99%
“…For example, the decay of 125 I has been shown to lead to the deposition of a very high dose (≈10 9 cGy/decaying atom) in the immediate vicinity (≈2 nm 3 ) of the decay site and a sharp and significant drop in the energy deposited (from ≈10 9 to ≈10 6 cGy) as a function of increasing distance (few nanometres) from the decaying 125 I atom (Kassis, 2011). For example, when 125 I is localized within the cytoplasm, the survival curve is of the low LET type and the number of decays needed to reduce survival is ≈80 times that of DNA-incorporated 125 I (Kassis, 2011 (Abbasi, 2012(Abbasi, , 2011Argyrou et al, 2013a;Bączyk, 2011;Bryan et al, 2009;Chakraborty et al, 2008;Daha et al, 2010;Das et al, 2009;Harrison et al, 2013;Lewington, 2005;Máthé et al, 2010;Neves et al, 2005;Nilsson et al, 2013bNilsson et al, , 2007Nilsson et al, , 2005aNilsson et al, , 2005bPandit-Taskar et al, 2014;Ramdahl et al, 2013;Sartor, 2004;Simón et al, 2012;Sivaprasad and Rajagopal, 2012;Tomblyn, 2012;Vigna et al, 2011;Volkert and Hoffman, 1999;Wang et al, 2011). Despite the growing number of radionuclides investigated for treatment of bone metastases, the use of 89 Sr and 153 Sm still accounts for the bulk of radiopharmaceutical bonetargeted therapeutics in the clinical context and the majority of the review articles available in the literature focus on those two radionuclides.…”
Section: Introductionmentioning
confidence: 99%
“…43 A phase 1 trial in both breast and prostate cancer patients showed that radium-233 was well tolerated at therapeutically relevant dosages, which led to the initiation of phase 2 trials. 44 In these trials, four intravenous injections of radium-233, Figure 1 Cancer-targeted therapies in malignant bone disease. Sotatercept binds activin A and thereby prevents its inhibitory effects on osteoblasts and prosurvival effects on osteoclasts.…”
Section: Mtor Inhibitionmentioning
confidence: 99%